Determinants of Stress Levels and Behavioral Reactions in Individuals With Affective or Anxiety Disorders During the COVID-19 Pandemic in Russia - Sorokin, Mikhail Yu; Kasyanov, Evgeny D.; Rukavishnikov, Grigory V.; Khobeysh, Maria A.; Makarevich, Olga V.; Neznanov, Nikolay G.; Maximova, Tatyana G.; Verzilin, Dmitry N.; Lutova, Natalia B.; Mazo, Galina E. (Frontiers in Sociology, 2022)
Individuals with affective and anxiety disorders are among those most vulnerable to the negative effects of the COVID-19 pandemic. Aim: to analyze the determinants of stress levels and protective behavioral strategies associated with the COVID-19 pandemic in Russian-speaking people with affective or anxiety disorders (AAD). Materials and methods. In this cross-sectional online survey, the psychological distress and behavioral patterns of respondents with self-reported AAD (n=1375) and without disorders (n=4278) were evaluated during three periods of restrictive measures in Russia (March – May, 2020). Distress levels were verified using the Psychological Stress Measure (PSM-25). Results. Stress levels among respondents with AAD were higher at all study periods than for those with no mental disorder (Cohen’s d 0.8-1.6). The stress level increased (Cohen’s d=0.4) in adolescents (16-18 years) with AAD and remained the same in those without disorders; in youths (19-24 years) with and without disorders, an increase (Cohen’s d=0.3) and a decrease (Cohen’s d=0.3) in the stress were observed, correspondingly; the stress in adults (25-44 years) with disorders did not change and decreased in those without disorders (Cohen’s d=0.4). Individuals with bipolar disorders demonstrated lower stress than individuals with depressive (Cohen’s d=0.15) and anxiety disorders (Cohen’s d=0.27). Respondents with depressive and bipolar disorders employed fewer protective measures simultaneously and were less likely to search for information about COVID-19. Conclusion. The presence of affective or anxiety disorders is associated with a more acute response to the COVID-19 pandemic. Apparently, the type of mental disorder influenced stress levels and protective behavior patterns.